Perceptions of police training needs in cyber-crime. (March 2022) - Harkin, Diarmaid; Whelan, Chad
A common observation in the literature on cyber-crime policing is the need for more training. However, there is little detail of who within the police organisation requires training and what type of training may be needed. Based on survey and interview data from three specialist cyber-crime units in Australia, this article identifies that 'lack of training' is likely to have distinct meanings for different groups within the police: (a) front-line officers, (b) higher management, (c) generalist investigators, and (d) specialist investigators and civilians in cyber-crime units. Each of these groups is likely to face unique training needs that undermines the overall effectiveness of police organisations to respond to cyber-crime. The article explores the perceived training requirements across each of these groups and some potential ways in which they can be addressed in an effort to stimulate further research in this area focusing on the differentiated internal needs of police organisations.